Pengaruh Risiko Likuiditas , Cadangan Kas dan Risiko NPL terhadap Profitabilitas Perbankan selama Covid-19 - Angelia Dwi Siskawati (Jurnal Kompetitif Bisnis, 2020)
This journal aims to determine the effect of Liquidity Risk, Cash Reserves and NPL Risk on Banking Profitability during the Covid-19 pandemic. Corona virus outbreaks impacted on various industrial sectors resulting in economic downturn, especially impacting the performance of banks in Indonesia. Bank performance can be seen from various sides, one of which is financial performance. In measuring the financial performance of a bank, profitability is one indicator that can be used The level of profitability of a bank can be influenced by internal and external factors. ROA or Return on Assets is a measurement of profitability. One internal factor that can affect bank profitability is liquidity. In addition there are several other factors discussed in this journal, namely factors that can be managed by banks, among others, cash reserves and Non-Performing Loans (NPL).